LRRK2 and Protein Aggregation in Parkinson’s Disease: Insights From Animal Models - Dues, Dylan J.; Moore, Darren J. (Frontiers in Neuroscience, 2020)
Mutations in leucine-rich repeat kinase 2 (LRRK2) instigate an autosomal dominant form of Parkinson’s disease (PD). Despite the neuropathological heterogeneity observed in LRRK2-PD, accumulating evidence suggests that alpha-synuclein and tau pathology are observed in a vast majority of cases. Intriguingly, the presence of protein aggregates spans both LRRK2-PD and idiopathic disease, supportive of a common pathologic mechanism. Thus, it is important to consider how LRRK2 mutations give rise to such pathology, and whether targeting LRRK2 might modify the accumulation, transmission, or toxicity of protein aggregates. Likewise, it is not clear how LRRK2 mutations drive PD pathogenesis, and whether protein aggregates are implicated in LRRK2-dependent neurodegeneration. While animal models have been instrumental in furthering our understanding of a potential interaction between LRRK2 and protein aggregation, the biology is far from clear. We aim to provide a thoughtful overview of the evidence linking LRRK2 to protein aggregation in animal models.